CHILD PROTEIN SCORE AS AN INDICATOR OF STUNTING RISK - Antun Rahmadi; RR Ratnasari Dyah Purnomowati (Jurnal Gizi dan Pangan Soedirman, 2026)
Stunting remains a major nutrition problem in Indonesia with a prevalence of 19.8% (SSGI, 2024). Protein quality is crucial for linear growth, yet assessments usually focus on intake quantity or diversity rather than biological value. This study aimed to develop and validate the Child Protein Score (SPMB) as a practical tool to assess protein quality and its link to stunting. A cross-sectional study was conducted among 109 children aged 6–59 months in the working area of the Kemalo Abung Public Health Center, North Lampung, using consecutive sampling. The sample consisted of 49 stunted and 60 non-stunted children. Stunting was defined by height-for-age z-score, and SPMB was calculated using a Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Data were analyzed with chi-square, logistic regression, and ROC curve. Stunted children showed lower SPMB compared to non-stunted (2.4 ± 1.1 vs 3.9 ± 1.2; p < 0.001). ROC analysis yielded an AUC of 0.79 (95% CI: 0.71–0.87; p < 0.001) with cut-off ≤3, and logistic regression showed a 3.3-fold higher risk of stunting in children with TFPS ≤3 (OR = 3.30; 95% CI: 1.50–7.50; p = 0.004). The SPMB proved valid, discriminative, and practical, supporting its use as a screening tool for stunting risk in primary care.